Fast-response measurements of organic trace species in the Earth's atmosphere - Geiger, Felix (KIT Scientific Publishing, 2014)
This work describes the development of an ultra-light-weight Proton-Transfer-Reaction Mass Spectrometer (PTR-MS), its detailed qualification, ground-based and airborne applications and studies on VOC emissions in connection with fossil fuel production. The new system was used aboard a mobile laboratory in order to investigate the chemical fingerprints of the diverse emitters at oil and natural gas well pads. Emissions of aromatic hydrocarbons at a hydraulically fractured well have been studied.